Intellectual Property Rights: Talking Points for RP-US FTA Negotiations - Delia S. Tantuico; Errol Wilfred Zshornack (Philippine Institute for Development Studies (PIDS), 2006)
Intellectual property rights-copyrights, trademarks, patents, trade secrets, and related rights-have become increasingly important with the advent of increased international trade, global and knowledge-based economy and fast developing technology. A strong intellectual property rights regime is necessary in order to attract foreign trade and direct investments. For this reason, the protection of intellectual property rights has become an important negotiating item in all FTAs which the United States has entered into. In view of the proposed RP-US FTA negotiations, this paper seeks to determine whether the existing intellectual property regime in the Philippines provides adequate and sufficient legal protection of intellectual property rights. It also seeks to determine whether the administrative and judicial processes are adequate and speedy and acceptable in the enforcement and protection of said rights in the light of FTAs already entered into by the United States with other countries, in general, and with Singapore, in particular, which will be the benchmark for the RP-US FTA. Other relevant issues in the protection of intellectual property rights such as the annual review of ountries by the United States Trade Representative in relation to Special 301 of the U.S. Trade Law; piracy of optical media, including books and pharmaceuticals; and the Trade-Related Aspects of Intellectual Property Rights (TRIPS) are also discussed. The author proposes certain provisions to be added to the Intellectual Property Code; sustained, consistent and stricter implementation of intellectual property laws including more efforts at curbing piracy; and more importantly, a strong political will and a strong determination to strengthen intellectual property rights, as necessary to make the IPR regime up to par with U.S. and international.
Keywords: 330; World Trade Organization; investment; intellectual property rights; market access; trade-related aspects of intellectual property rights (TRIPS); dispute settlement; Optical Media Act; E-commerce Law; legal protection; capability building; free trade agreements (FTAs); Immaterialgüterrechte; Internationale Schiedsgerichtsbarkeit; Auslandsinvestition; Internationale Wirtschaftsbeziehungen; Freihandelszone; Philippinen; USA; TRIPS